2019
DOI: 10.1371/journal.pone.0210136
|View full text |Cite
|
Sign up to set email alerts
|

Common causes of EID sample rejection in Zimbabwe and how to mitigate them

Abstract: Early infant diagnosis (EID) of HIV provides an opportunity for early HIV detection and access to appropriate Antiretroviral treatment (ART). Dried Blood Spot (DBS) samples are used for EID of exposed infants, born to HIV-positive mothers. However, DBS rejection rates in Zimbabwe have been exceeding the target of less than 2% per month set by the National Microbiology Reference Laboratory (NMRL), in Harare. The aim of this study was to determine the DBS sample rejection rate, the reasons for rejection and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…The second type of preanalytical error in this study was referring to an uncentrifuged specimen, which accounted for 20.4 % of the total errors. This finding is nearly identical to the result of a study done in Nepal, which found that 20 % of specimens were rejected due to not being centrifuged on a timely base [ 16 ]. This result, however, is lower than the study conducted at the Amhara Public Health Institute in Bahir Dar, Ethiopia, at 46.9 % [ 9 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The second type of preanalytical error in this study was referring to an uncentrifuged specimen, which accounted for 20.4 % of the total errors. This finding is nearly identical to the result of a study done in Nepal, which found that 20 % of specimens were rejected due to not being centrifuged on a timely base [ 16 ]. This result, however, is lower than the study conducted at the Amhara Public Health Institute in Bahir Dar, Ethiopia, at 46.9 % [ 9 ].…”
Section: Discussionsupporting
confidence: 88%
“…Of the total specimens collected the overall specimen rejection rate found in the current study is similar to the overall specimen rejection rates obtained from studies done at the University of Gondar Hospital, Northwest Ethiopia, 3.8 % [ 15 ]; in Zimbabwe, 4 % [ 16 ], and Nepal, 5.5 % [ 17 ]. However, the overall sample rejection at the pre-analytical phase in the current study is higher than the studies conducted at Amhara Public Health Institute in Bahir Dar, Ethiopia, 0.5 % [ 9 ]; St. Paul's Hospital Millennium Medical College in Addis Ababa, Ethiopia, 1.4 % [ 1 ]; Delhi, 1.52 % [ 18 ]; Cantonal Hospital Zenica, 1.7 % [ 19 ]; and Makkah, Saudi Arabia, 1.3 % [ 20 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Common user errors with self-test kits include errors in positioning the sampling devices for the test, carrying out the steps in the right order, following the test times correctly, errors in interpreting the results (Seidahmed et al 2008), and users failing to refer to the instructions altogether (Weinhold et al 2018). Other common errors are errors in transferring a set volume of test sample (Incardona et al 2018), and collecting insufficient sample volume, which results in blood spot samples being rejected (Govender et al 2016, Chiku et al 2019. The clarity of user instructions for self-administered tests becomes even more crucial when we consider that tests need to work across cultures and with patients of varying reading ability.…”
Section: Instructions For Point-of-use Home Diagnostic Testing Kitsmentioning
confidence: 99%